Pengaruh Pendidikan Kesehatan dengan Media Poster terhadap Perilaku Pencegahan COVID-19 pada Sekaa Teruna Teruni - I Gusti Ketut Gede Ngurah; I Gusti Ayu Ngurah Viola Utami Dewi; I Ketut Gama (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2021)
It is very important to develop steps to prevent transmission of COVID-19 and break the chain of transmission through the provision of health education so that researchers are interested in examining whether there is an effect of health education with poster media on the behavior of preventing transmission of COVID-19 with the target of sekaa teruni teruni in the village/ Gilimanuk Village The research objective was to determine the effect of health education with poster media on the prevention behavior of COVID-1 in STT in Gilimanuk in 2021. This type of research was pre- experimental designs with one-group pre-posttest design. The study population numbered 250 people. The sampling technique used stratified random sampling, obtained a sample of 77 people. In this study, most of the behaviors before being given health education were in the sufficient category (37.7%), the attitude was in the good category (62.3%), and the action was in the good category (35.1%). After health education was carried out, knowledge, attitudes and actions were in the good category. Hypothesis test used Wilcoxon statistical test, and the p- value was obtained in the Sig column. 2-tailed = 0.000 alpha (0.05). The conclusion is that there is a significant effect of health education with media posters on the prevention behavior of coronavirus disease (COVID-19) in STT. Suggestions for STT to implement preventive behaviors that have been given, and for future researchers to be able to develop similar research with other media.